Comparative analysis of disease burden in Sichuan Province in 2010 and 2020 based on disability-adjusted life years - WEN Xiaoyan; GUO Huimin; JIANG Wenlan; CHEN Li (Shanghai yufang yixue, 2023)
ObjectiveTo analyze the disease burden in Sichuan Province in 2010 and 2020， and to provide reference for disease prevention and control.MethodsMonitoring data on causes of death in Sichuan Province in 2010 and 2020 were collected. Disability-adjusted life years （DALY）， years of life lost （YLL） and years lived with disability （YLD） were calculated to assess the disease burden in Sichuan Province.ResultsIn 2020， DALY was 7.004 0 million years， among which YLL and YLD were 3.719 6 million and 3.284 4 million， respectively. Compared with 2010， the total DALY in 2020 increased by 8.27%， most of which came from the increase of YLL （16.66%）. In 2020， the standardized total DALY rate was 69.91‰， which decreased by 9.87% compared with 2010. Specifically， the rate decreased by 15.87% for females and 5.28% for males. In 2020， the burden of DALY disease in the elderly over 60 years old increased by 34.55% compared with 2010. The burden of infectious and maternal diseases decreased the most， and the standardized DALY rates of male and female in 2020 decreased by 47.03% and 55.50% compared with 2010， respectively. Injury was the next most important factor， which decreased by 32.97% in males and 26.92% in females. The standardized DALY rate of chronic diseases increased by 5.41% in males and decreased by 10.67% in females. In 2020， compared with 2010， the standardized DALY rate of males increased significantly in diabetes （82.02%）， nervous system and mental disorders （26.31%）， and cardiovascular and cerebrovascular diseases （19.86%）. Among women， significant increases were seen in diabetes mellitus （54.74%）， neurological and mental disorders （35.52%）， and musculoskeletal and connective tissue diseases （23.51%）.ConclusionThe overall disease burden in Sichuan Province shows a declining trend， mainly attributed to the decrease in infectious and maternal diseases and injuries. The disease burden among people over 60 years old has increased significantly， with the focus on chronic diseases such as diabetes， cardiovascular and cerebrovascular diseases， nervous system and mental disorders， and musculoskeletal and connective tissue diseases.